Οι ποιητές της Θεσσαλονίκης 1930-1980 (Θύραθεν, 2016)
Ανθολογούνται: Βαφόπουλος,Παυλέας,Καρέλλη,Πεντζίκης,Θέμελης,Στογιαννίδης,Βαρβιτσιώτης,Αναγνωστάκης.Κύρου,Θασίτης,Χριστιανόπουλος,Ιωάννου,Ασλάνογλου,Ευαγγέλου,Μάρκογλου,Κέντρου-Αγαθοπούλου,Θεοδωρίδης,Καραγιάννη,Καρατζόγλου,Νικηφόρου,Καλοκύρης,Τραιανός,Βιστωνίτης,Ίσαρης,υφαντής,Ξεξάκης.